PENGARUH MODERN MARKETING MANAGEMENT TERHADAP KEPUASAN KONSUMEN MEMBELI HANDPHONE SAMSUNG PADA BRAND STORE SAMSUNG DI KOTA PALU - Lele, Aco (Katalogis, 2017)
This study aims to identify and analyze: 1) the level of importance of Modern Marketing Management variable that includes People, Process, Programs and Performance to meet customer’s satisfaction in Samsung Mobile Phones purchasing at Samsung Brand Store in Palu City; 2) significant influence of Modern Marketing Management (People, Process, Programs and Performance) simultaneously and partially on customer’s satisfaction in Samsung Mobile Phones purchasing at Samsung Brand Store in Palu City. Sampling technique used in Non-probability Sampling by applying incidental sampling method to select 150 respondents, who shopped Samsung mobile phones more than once. Method of analysis applied are Statistical Product and Service Solution (SPSS) and Importance Performance Analysis (IPA). The result of IPA method indicate that: 1) in quadrant A, variable that need to be improved are programs and performance; in quadrant B, variable needs to be maintained is people; in quadrant C, the variable that shows low performance but do not require urgent action is process. It is suggested that the focus of the company should be on quadrant A; 2) the variable of Modern Marketing Management (People, Process, Programs and Performance) simultaneously have positive and significant influence on customer’s satisfaction in Samsung Mobile Phones purchasing at Samsung Brand Store in Palu City; 3) People, Process and Performance partially have positive and significant influence on customer’s satisfaction in Samsung Mobile Phones purchasing at Samsung Brand Store in Palu City, while programs has a positive but insignificant influence on customer’s satisfaction in Samsung Mobile Phones purchasing at Samsung Brand Store in Palu City.